Diversity Weed of plantation Oranges (Citrus nobilis Lour.) with Different Ages in Lima Puluh Kota Regency. - Solfiyeni, Solfiyeni; Mardianti, Yomita (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Abstract: Weeds in citrus plantation areas create competition with staple plants for water, nutrients, light and can even compete with staple crops by releasing allelochemical compounds (allelopathy). This research aims to determine the composition and structure of weeds in Jesigo orange (Citrus nobilis Lour.) plantations of different ages in Gunuang Omeh sub-district, Lima Puluh Kota district, West Sumatra province. This research was carried out using the quadratic method by placing plots using purposive sampling in orange plantations aged 10 years and aged 1.5 years. At both locations plots measuring 10x10 meters were created which were divided into 25 subplots measuring 2x2 meters. In each subplot, observations were made of weed species and the number of individuals of each species. Data analysis was carried out using the important value index formula, Shannon-Wienner Diversity Index and Sorensen Similarity Index. The results of the research in orange plantations aged 10 years found 6 families, 15 genera, 15 species and 889 individual weeds, while in orange plantations aged 1.5 years, 7 families, 14 genera, 14 species and 588 individual weeds were found. The dominant weed in orange plantations aged 10 years is Aeschynomene indica with an important value index (IVI) of 23.84% and in orange plantations aged 1.5 years is Melastoma malabathricum with an IVI of 19.15%. The value of the species diversity index (H') in orange plantations aged 10 years is 2.49 and in orange plantations aged 1.5 years is 2.34, which indicates that the species diversity at both locations is classified as moderate. The similarity index value for both plantations is 13.8%. The composition and structure of weeds in orange plantations aged 10 years and 1.5 years old are different and the similarity of weed species in both locations is low.